Adding energy minimization strategy to peptide-design algorithm enables better search for RNA-binding peptides Redesigned λ N peptide binds boxB RNA - Xiao, Xingqing (Journal of computational chemistry, 2016)
© 2016 Wiley Periodicals, Inc.